Hip replacement at posttraumatic defects of coxal cavity - A. N. Grischuk; I. V. Usoltsev (Acta Biomedica Scientifica, 2015)
From 2009 to 2014 total hip replacement on the account of posttraumatic coxarthrosis of the of the 3rd degree in combination with coxal cavity defect, dislocation or incomplete dislocation of femoral head was conducted in our clinic in 12 patients (10 (83,3 %) men and 2 (16,7 %) women) of 23-51 years (42 on the average). It took from 3 weeks to 8 years (26 months on the average) from the moment of trauma till the operation. We used the method of the replacement of defect of posterosuperior edge of coxal cavity of femoral head. We used acetabular components of cementless fixation in 3 (25 %) cases and mounted a cup of cement-retained fixation in 9 (75 %) cases. The operation lasted from 45 to 225 minutes (90 minutes on the average). Blood loss was from 500 to 2100 ml(1100 ml on the average). 3 (25 %) patients had complications in postoperative period. 2 (16,7 %) patients in consequence of noncompliance of orthopedic regimen had dislocation of prosthesis head on the 8th and 14th day after the operation. 1 (8,3 %) patient had soft tissues infection in the zone of operative intervention in postoperative period. Terms of observation of alteration of massive autografts and functional results of hip replacement were from 1 to 5 years. 11 (91,7 %) patients didn't have any signs of acetabular component instability and osteolysis in the zone of contact between bone cavity and cup. No patient had signs of instability of stem of joint. Harris score increased from 34,1 ± 7,2 to 78 ± 8,4 points.